Multifunctional laminarin microparticles for cell adhesion and expansion - Martins, C. R. (2018)
Microfabrication technologies have been widely explored to produce microgels that can be assembled in functional constructs for tissue engineering and regenerative medicine applications. Here, we propose microfluidics coupled to a source of UV light to produce multifunctional methacrylated laminarin microparticles with narrow distribution of sizes using photopolymerization. The multifunctional microparticles were loaded with platelet lysates and further conjugated with an adhesive peptide. The adhesive peptides dictated cell adhesiveness to the laminarin microparticles, the incorporation of platelet lysates have resulted in improved cell expansion compared to clear microparticles. Overall, our findings demonstrate that multifunctional methacrylated laminarin microparticles provide an effective support for cell attachment and expansion. Moreover, expanded cells provide the link for microparticles aggregation resulting in robust 3D structures. This suggest the potential for using the methacrylated laminarin microplatforms capable to be assembled by the action of cells to rapidly produce large tissue engineered constructs.